Employing the historical tale in contemporary Emirati poetry: Diwan " To whom do you seek refuge, Buthain?" The poet Salha Ghabish as a model - Almansoori, Moza Mohammed; Darabseh, Mahmoud Muhammad; Al-Qudah, Mohammad Ahmad (Al-Adab Journal, 2022)
The Diwan of the Emirati poet, Salha Ghabish, demonstrated the ability of the contemporary Emirati poet to deal with heritage in its various dimensions, employing the story of Buthaina, the Andalusian princess, which is teeming with events and personalities according to different styles, to express the present, and to convey contemporary visions and political, social and personal reasons. The use of this tale came entirely in the threshold of the title, and some of the poems of the Diwan, and partly to support a certain idea in other poems. The poet started from a heritage structure, and transcended it historically and intellectually, until the employment of narrative heritage became part of an aesthetic and intellectual vision, according to a human and civilized perspective.In the Diwan “To whom do you seek refuge, Buthain?” The poet Salihah Ghabish’s employment of the historical tale and its linking to the poet’s self, has added depth to the text’s vision of a contemporary historical aspect, as the poet linked the ancient historical tale with its contemporary reality with a personal and subjective renewal. The employment of Buthaina's tale was a harnessing of the connotations inherent in it and linking it to contemporary reality.The historical narrative heritage was a factor that built the contents of the contemporary Arabic poem, which enriched the poetic experience, and gave it depth of knowledge and artistic intensity. The story became a focus through which the poet sees his turbulent inner world, in his talk about the self, the homeland, the conscience and the human being. The use of the tale was a symbol that gives the poetic text human dimensions.Thus, the tale remained a collective memory and a firm belief that is transmitted from generation to generation, and its use in contemporary poetry was a retrieval of history, to play the role of preserving the old heritage from loss, and then resurrecting it again in a contemporary manner.Thus, the contemporary poet's employment of the historical tale became a new reading of history from the perspective of contemporary reality, and the treatment of reality using historical events in an artistic, symbolic and aesthetic style.